The Zero Sign on Inscriptions and Manuscript Based on the Historical Supply Chain Management: A Case Study of Indonesia Archipelago before Majapahit Era - Prabowo, Agung; bin Mamat, Mustafa; Sukono, Sukono (International Journal of Supply Chain Management, 2019)
The widespread recognition of the term “supply chain” has come primarily as a result of the globalization of manufacturing since the mid 1990s, particularly the growth of manufacturing in China. U.S. imports from China grow. Indonesian people have been acquainted with the place value and a base of 10 and have used them since the early 5th century. The place value is related to the number of positions on units, tens, hundreds and so on. A base of ten number is similar to the digits of the numbers 0, 1, 2,…, 9 that should be inserted into each of the place value. This paper observes the existence of 0 digits that is used in Nusantara, in specific, by gaining some sources in the inscriptions, temples, gravestones, and coins shapes. This article is written as the result of an observation by using literary observation method; in the inscription shape whose aim research to give the evidence that the number 0 has been used in Nusantara. As a result, the 0 digits have been first discovered in Sumatera; it was on Kedukan Bukit inscription numbered 604 Saka (682 C.E.) The existence of the zero number has also been discovered in the original Nusantara numbers.